2000
DOI: 10.1038/sj.cgt.7700215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of herpes simplex virus thymidine kinase in combination with cytokine gene therapy in an experimental metastatic breast cancer model

Abstract: Immunotherapy in combination with suicide gene therapy for breast cancer was tested using a metastatic animal model. Subcutaneous injection of the nonimmunogenic breast cancer cell line 4T1 in BALB/C mice gave rise to tumors in 100% of mice with both micrometastases and macrometastases in the lung. We used the herpes simplex virus thymidine kinase (HSV-TK) gene along with the cytokine genes granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-2 (IL-2) to determine their effect on tumor reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
3
32
1
Order By: Relevance
“…Tumor size was determined employing the formula used to calculate the volume of an ellipsoid body (L × W × H/2, where L = length, W = width, H = height, or L × (W) 2 /2, when W = H). 52 In vivo gene therapy using adenoviral vectors Ten-day-old subcutaneously grown 143B tumors were injected with 9.6 × 10 8 p.f.u. of hTERTp/TK or CMVp/TK adenoviruses.…”
Section: Adenoviral Transduction In Vitromentioning
confidence: 99%
“…Tumor size was determined employing the formula used to calculate the volume of an ellipsoid body (L × W × H/2, where L = length, W = width, H = height, or L × (W) 2 /2, when W = H). 52 In vivo gene therapy using adenoviral vectors Ten-day-old subcutaneously grown 143B tumors were injected with 9.6 × 10 8 p.f.u. of hTERTp/TK or CMVp/TK adenoviruses.…”
Section: Adenoviral Transduction In Vitromentioning
confidence: 99%
“…20 The effectiveness of this combination was also demonstrated for murine colon cancer, 21 melanoma, 22 gastric 23 and breast cancer. 24,25 Therefore, repeated injections of both SG system and cytokine-secreting xenogeneic cells into the tumor bed could be a powerful strategy to prevent relapse and thus support a longer immune response with a stronger antitumor memory.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the "bystander effect" induced by tk gene can also enhance the tumor-killing capacity of the HSVtk/GCV system. [25][26][27] However, it was found in some investigations that the anti-tumor efficiency of this system was limited by the lower rate of gene transfection and their insufficient induction of host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 26 reported that cytokine gene IL-2 could act synergistically with the suicide gene to induce a systemic anti-tumor immunity. In another study, Majumdar and his associates 27 have compared the therapeutic effect of IL-2 expression alone with that by the coexpression of IL-2 and tk genes on squamous cell carcinoma in nude mice, and found that the combined gene expression was most efficient for the gene therapy. Unfortunately, there have been few In the present study, we tried to observe the anti-tumor effects by the coexpression of suicide gene HSVtk and cytokine gene TNF-α on gastric carcinoma cell lines SGC7901.…”
Section: Discussionmentioning
confidence: 99%